The impact of agility on the market performance of born-global firms: an exploratory study of the ‘Tech City’ innovation cluster - Nemkova, Ekaterina (Elsevier, 2017)
Although there is some recognition that agility is advantageous for a born-global firm, the concept of agility is underexplored in the management and marketing literature. Little is known about the ability of born-globals to become agile and under what conditions agility can lead to better market performance. In this investigation the exploratory qualitative research was conducted using the data of fifteen in-depth interviews with managers and experts in Tech City in London, UK. Firstly, the findings show that creativity and informal planning are the main decision-making drivers of agility in born-global firms. Secondly, the study reveals that agility is more likely to be positively related to international market performance when key decision-makers have certain skills, including knowledge of the market, international experience, learning orientation and ambiguity tolerance.